THE ROLE OF PUBLIC SERVICE QUALITY AND SMART GOVERNANCE IMPLEMENTATION IN PUBLIC SATISFACTION: AN EMPIRICAL STUDY AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF LANGKAT REGENCY - Muhammad Rafi Indra Putra; Meilita Tryana Sembiring; Iskandarini Iskandarini (Journal Analytica Islamica, 2026)
This study is motivated by the importance of improving public service quality and implementing smart governance to enhance community satisfaction, particularly at the Department of Population and Civil Registration of Langkat Regency. The main problem addressed in this study is the extent to which public service quality and smart governance implementation influence community satisfaction. This research employs a quantitative approach using a survey method involving 205 respondents. Data analysis techniques include validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that public service quality has a positive and significant effect on community satisfaction, and smart governance implementation also has a positive and significant effect. Simultaneously, both variables significantly influence community satisfaction, with a model explanatory power of 69%. These findings suggest that service quality remains the dominant factor in improving community satisfaction, while smart governance acts as a supporting factor that enhances the effectiveness of public services. The implication of this study emphasizes that improving community satisfaction requires synergy between high-quality services and the utilization of technology in governance. Therefore, the integration of conventional and digital services is a crucial strategy to achieve effective, efficient, and citizen-oriented public service delivery.